Using a systematic approach to synthesize existing knowledge on Gymnopus fusipes (syn. Collybia fusipes), the cause of Collybia root rot. Issue 5 (5th October 2022) - Pettifor, Bethany J.; Denman, Sandra; McDonald, James E.
Abstract: Gymnopus fusipes (syn. Collybia fusipes ; syn. Agaricus fusipes ) is an agaricomycete fungus known to cause root rot on a number of economically important tree species, including oak, where it has been linked to the development of chronic oak decline. Due to lack of correlation between above‐ground decline symptoms and G. fusipes infection, its presence can often go undiagnosed until mortality. Although G. fusipes was first described over 200 years ago, there is still a paucity of information on the biology and ecology of this species, which represents a barrier to understanding its impacts on tree health. The aim of this review was to synthesize existing knowledge on the biology, ecology, host range and host interactions of G. fusipes . Using a systematic search, five online databases were used to obtain published literature resulting from the search terms ' Gymnopus fusipes ', ' Collybia fusipes ' and ' Agaricus fusipes '. After a strict filtering process, the papers were examined for data pertaining to the biochemistry, distribution, ecology, genomic information, host range, infection biology, morphology and phylogeny of the species. The results reveal that there is a large amount of ambiguous and sometimes spurious citation of G. fusipes in the literature. However, it can be confirmed that G. fusipes is a facultative saproparasite, found in several countries, mainly in Europe, and is associated with several socioeconomically important host species, including oak, chestnut, and fir. Gymnopus fusipes has repeatedly been investigated with regard to oak decline in Europe, where it is believed to play a crucial role in the early stage of decline development. Key knowledge gaps highlighted in this review include a lack of information on the basic biology of the species, including its life cycle, which is crucial to fully understanding G. fusipes infection and epidemiology. Further work is needed to assess G. fusipes distribution, phylogeny and host range through molecular identification. There is also a need to characterize the pathogen–host interaction at a molecular level, with identification of active genes and therefore the mechanisms of infection. A combination of culture‐based and molecular techniques should be utilized in order to close these key knowledge gaps.